2021
DOI: 10.3389/fmed.2021.812693
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internal Limiting Membrane Flap for Highly Myopic Macular Hole Retinal Detachment: Improving the Closure Rate but Leading to Excessive Gliosis

Abstract: Purpose: To investigate the surgical outcomes of the inverted internal limiting membrane (ILM) flap technique for macular hole retinal detachment (MHRD) in high myopia.Methods: This was a retrospective interventional study on 45 highly myopic eyes with MHRD after ILM peeling (n = 24, peeling group) or the inverted ILM flap technique (n = 21, inverted group). The inverted group was consisted of autologous blood (AB) subgroup (n = 10) and perfluorocarbon liquid (PFCL) subgroup (n = 11). MH closure, best-correcte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, the BCVA between closed MH and unclosed MH was not significantly different, which was in line with other studies. [13,21,25] Previous studies have shown that ELM and EZ restoration was associated with improvement of postsurgical BCVA [26]. However, the outer retinal layer was difficult to identify in our study due to chorioretinal atrophy, indicating that irreversible damage had occurred in the photoreceptor layer.…”
Section: Discussionmentioning
confidence: 60%
“…However, the BCVA between closed MH and unclosed MH was not significantly different, which was in line with other studies. [13,21,25] Previous studies have shown that ELM and EZ restoration was associated with improvement of postsurgical BCVA [26]. However, the outer retinal layer was difficult to identify in our study due to chorioretinal atrophy, indicating that irreversible damage had occurred in the photoreceptor layer.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, retraction of the outer layer of Mu¨ller cells that envelops the photoreceptor cells can lead to centrifugal displacement of photoreceptor cells. 33 In the temporal inverted ILM flap technique, a large monolayer ILM flap provides a more stable structure for glial cell proliferation. As glial cells present and adhere to the ILM flap, sticking to the retinal surface due to ILM turnover and being unable to migrate to the fully sealed MH space, the proliferation of glial cells within the MH wall also has an important role in MH closure.…”
Section: Discussionmentioning
confidence: 99%
“…However, a proliferative response has also been observed after the classic inverted ILM flap technique. Chen et al 13 described a series of 45 eyes with myopic MH and RD. Twenty-four eyes were treated with ILM peeling, and 21 eyes were treated with the inverted ILM flap technique.…”
Section: Discussionmentioning
confidence: 99%